Análise dos atores institucionais em iniciativas de economia criativa de artesanato em João Pessoa (PB) - Silva, Claudyvanne dos Santos Nascimento (2023)
The topic of the creative economy and the development of artisan-entrepreneurs has been increasingly debated, as it addresses fundamental issues for economic and social growth. By promoting public policies and actions aimed at strengthening the artisanal sector, it is possible to boost income generation, local entrepreneurship, cultural recognition, and poverty reduction, contributing to sustainable local growth. In this context, this study intended to associate Creative Economy, Cultural Entrepreneurship and Crafts Studies from an Organizational Institutionalism perspective, since, through this articulation it is possible to investigate the interactions between culture and economy in institutional actors' responsibilities and commitments in the development of artisan-entrepreneurs. The goal of this research was to understand the performance of institutional actors involved in the context of developing initiatives by artisan-entrepreneurs in João Pessoa (PB). To achieve this goal, it was initially necessary to identify the context of creation and the history of development of creative craft economy initiatives in the city of João Pessoa (PB). Secondly, we sought to characterize the actions of institutional actors focused on the artisan-entrepreneurs development process. Finally, the performance of institutional actors involved in the development of artisan-entrepreneurs in João Pessoa (PB) was analyzed. This research adopted a qualitative methodological approach, carrying out empirical research supported by primary and secondary data, such as interviews, observations, documentary research and informal conversations, applying qualitative content analysis to the empirical material. Results indicate that Public Management, SEBRAE and UFPB, each in its own specificity, favored the context of emergence and strengthening of the creative economy of João Pessoa (PB), through institutional work carried out in the following ways: (i) Public Management carrying out political institutional work, through political negotiation, decision-making, creation of public policies and establishment of legal instruments; (ii) SEBRAE carrying out technical institutional work through technical support and incentives for the adoption of good management and commercial practices; and, (iii) UFPB also carrying out technical institutional work based on efforts to theorize existing practices. Particularly, the Public Power stands out, as it is the institutional actor that supports the regulation of this productive activity, making it possible to understand which elements of the political context impact the normative orientation of the sector. Furthermore, the public policies implemented played a significant role in this scenario, although the analysis showed that management changes influence the interest in promoting craftsmanship in João Pessoa (PB). Thus, it was possible to conclude that the practice of institutional actors influences the development of artisan-entrepreneurs, whether through public policies or through other economic and educational measures, highlighting that the implementation of these measures requires the engagement and collaboration of all actors involved, including public authorities, academic institutions, private sector entities and civil society.